Taxonomy of the order Mononegavirales: update 2016 - Afonso, Claudio L.; Amarasinghe, Gaya K.; Bányai, Krisztián; Bào, Yīmíng; Basler, Christopher F.; Bavari, Sina; Bejerman, Nicolás; Blasdell, Kim R.; Briand, François-Xavier; Briese, Thomas; Bukreyev, Alexander; Calisher, Charles H.; et al. (Archives of virology, 2016)
In 2016, the order Mononegavirales was emended through the addition of two new families ( Mymonaviridae and Sunviridae ), the elevation of the paramyxoviral subfamily Pneumovirinae to family status ( Pneumoviridae ), the addition of five free-floating genera ( Anphevirus , Arlivirus , Chengtivirus , Crustavirus , and Wastrivirus ), and several other changes at the genus and species levels. This article presents the updated taxonomy of the order Mononegavirales as now accepted by the International Committee on Taxonomy of Viruses (ICTV).